Age-Influenced Receptors of Advanced Glycation End Product Overexpression Associated With Osteogenic Differentiation Impairment in Patients With Type 2 Diabetes - Phimphilai, Mattabhorn; Pothacharoen, Peraphan; Kongtawelert, Prachya (Frontiers in Endocrinology, 2021)
Preclinical studies have found impaired osteogenic differentiation to be associated with type 2 diabetes (T2DM), which is related to skeletal accumulation of advanced glycation end products (AGEs). Our previous study also showed impaired osteogenic differentiation in peripheral blood-derived mononuclear cells (PBMC) isolated from patients with long-standing T2DM, which is conceivably due to the overexpression of receptor of advance glycation end products (RAGE) and the enhancement of cellular apoptosis. However, the existence of RAGE overexpression in earlier stages of diabetes remains unclear, as do the factors influencing that RAGE overexpression. This cross-sectional study enrolled 40 patients with T2DM treated with metformin monotherapy and 30 age-matched non-diabetic controls (NDM) to investigate the overexpression of RAGE in PBMC derived from patients with earlier stage diabetes, as well as to explore its determining factors. Almost all (90%) PBMC-isolated from NDM (NDM-pD) expressed osteoblast-specific genes including ALPL, BGLAP, COL1A1, and RUNX2/PPAR while only 40% of PBMC-derived from diabetic patients (DM-pD) expressed those genes. By using age- and pentosidine-matched NDM-pD as a reference, AGER and BAX/BCL2 expression in PBMC isolated from diabetic patients showing impaired osteoblast-specific gene expression (DM-iD) were 6.6 and 5 folds higher than the reference while AGER and BAX/BCL2 expression in DM-pD were comparable to the reference. AGER expression showed a significant positive correlation with age (r=0.470, p=0.003). The multivariate analysis demonstrated that both age and AGER expression correlated with the potential for osteogenic differentiation in the PBMC isolated from patients with diabetes. In conclusion, this study showed osteogenic differentiation impairment in approximately half of PBMC derived from type 2 diabetic patients receiving metformin monotherapy. Both AGER and BAX/BCL2 overexpression were demonstrated only in PBMC-isolated from diabetic patients with poor osteogenic differentiation. Therefore, this study not only illustrated the existence of RAGE overexpression in PBMC derived from patients with early stages of T2DM but also strengthened the linkage between that RAGE overexpression and the retardation of osteogenic differentiation. Age was also shown to be a positive influencing factor for RAGE overexpression. Furthermore, both age and RAGE overexpression were demonstrated as independent risk factors for determining osteogenic differentiation potential of the PBMC-isolated from T2DM.